(3eHGOF GdGbJUGO GdSjGSj (B:s (3GdGbJUGO GdfbOj (B/s - (3OhjOGQ, eMeOs ((3GdGScfOQjI(B: s (3OGQ GdLGeYI GdLOjOI(B, s, 2008)
1)(3dJYQja HGdfbhO(B:(3fTCI GdfbhO h JWhQgG eY GbJUGO GdeHGOdI , GdfbhOGHJOGAG ef GdbjeI h GdfXGe GdfbOj h GdfXGe GdfbOj GdeUQj (B2)(3GdeDSSGJ GdfbOjI (B: (3GdfXGe GdeUQaj aj Xd WQjbI GdGfJGL GdQCSeGdjI HJfGhd cd ef GdQCSeGdjIGdUfGYjI h fTCI GdfXGe GdeUQaj GdJfGaSj h JWhQ GdfXGe GdeUQaj GHJOGA ef efJUa GdbQf GdJGSY YTQ (B3)(3GdfbhO h fXQjGJ COGA GdGbJUGO GdQCSeGdj (B: (3GdfGJL GdGLJeGYj h cjajI MSGHg , GdfbhO h fXQjI GdcdGSjc aj COGA GdGbJUGO GdQCSeGdj h GdfXQjI GdfbOjI GdcjfRjI aj COGA GdGbJUGO GdQCSeGdj (B.s
Keywords: (3GdGbJUGO GdQCSeGdjs; (3GdGbJUGO GdSjGSjs; (3GdfbhOs